Blasenhalssklerose nach Prostataeingriffen: wann welche Therapie? = Bladder neck sclerosis following prostate surgery : which therapy when? - Rassweiler, Jens; Weiss, Hagen; Heinze, Alexander (Der Urologe, 2017)
Secondary bladder neck sclerosis represents one of the more frequent complications following endoscopic, open, and other forms of minimally invasive prostate surgery. Therapeutic decisions depend on the type of previous intervention (e.g., radical prostatectomy, TURP, HoLEP, radiotherapy, HIFU) and on associated complications (e.g., incontinence, fistula). Primary treatment in most cases represents an endoscopic bilateral incision. No specific advantages of any type of the applied energy (i.e., mono-/bipolar HF current, cold incision, holmium/thulium YAG laser) could be documented. Adjuvant measures such as injection of corticosteroids or mitomycin C have not been helpful in clinical routine. In case of first recurrence, a transurethral monopolar or bipolar resection can usually be performed. Recently, the ablation of the scared tissue using bipolar vaporization has been recommended providing slightly better long-term results. Thereafter, surgical reconstruction is strongly recommended using an open, laparoscopic, or robot-assisted approach. Depending on the extent of the bladder neck sclerosis and the underlying prostate surgery, a Y-V/T-plasty, urethral reanastomosis, or even a radical prostatectomy with new urethravesical anastomosis should be performed. Stent implantation should be reserved for patients who are not suitable for surgery. The final palliative measure is a cystectomy with urinary diversion or a (continent) cystostomy.
Englischer Paralleltitel von Frontdoor übernommen
Gesehen am 05.11.2018